2018
DOI: 10.5005/jp-journals-10005-1486
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus Type 1 on Lebanese Families’ Quality of Life

Abstract: IntroductionDiabetes mellitus type 1 (DM1) markedly alters the lives of individuals and their families. Family members can be affected by diabetes and its treatment, causing burden, distress, and reduced quality of life (QOL).ObjectiveThe aim of this research is to study the relationship between the diabetic child and the family members, to evaluate the stress and emotional issues between siblings, and to weigh in on the psychological, affective, and financial burden that parents have to deal with in their dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Few studies have examined parental career limitations in association with child diseases. In a small Lebanese study (n = 37), more than 80% of parents reported that their career has been affected by their child’s Type I diabetes [ 11 ], an estimate which is much higher than identified in our sample of families with food allergy. As such, future studies are warranted to explore if these findings persist in other populations, in order to identify policy needs that will directly benefit affected families.…”
Section: Mothers’ Career Limitations Attributed To Food Allergymentioning
confidence: 78%
“…Few studies have examined parental career limitations in association with child diseases. In a small Lebanese study (n = 37), more than 80% of parents reported that their career has been affected by their child’s Type I diabetes [ 11 ], an estimate which is much higher than identified in our sample of families with food allergy. As such, future studies are warranted to explore if these findings persist in other populations, in order to identify policy needs that will directly benefit affected families.…”
Section: Mothers’ Career Limitations Attributed To Food Allergymentioning
confidence: 78%
“…The oral complications affect diabetic children's quality of life and their families. 6 , 7 Therefore, prevention and early management of oral pathologies in diabetes care practice are crucial but remain a major challenge for diabetes care professionals. 8 10 …”
Section: Introductionmentioning
confidence: 99%
“…A previous study on balanced diabetic children (considered normal patients as their HbA 1c is <7) demonstrated that dental treatments are possible and safe while following strict measures. 11 …”
Section: Introductionmentioning
confidence: 99%